Physical oceanography during RV HEINCKE cruise HE580 - Moritz Sonnewald; Sandra Tippenhauer; Mario Hoppmann (PANGAEA, 2022)
Conductivity-temperature-depth profiles were measured using a Seabird SBE 911plus CTD during RV HEINCKE cruise HE580 between 2021-07-17 and 2021-07-30. Additional sensors included a WET Labs C-Star transmissometer and a WET Labs ECO-AFL fluorometer. Data were connected to the station book of the specific cruise as available in the DSHIP database. Processing of the data including removal of obvious outliers followed the procedures described in CTD Processing Logbook of RV HEINCKE (hdl:10013/epic.47427). A detailed report on the CTD data of HE580 is available at https://hdl.handle.net/10013/epic.794e4bc7-5cb4-4f51-8f42-97745b90204a.